Programación por imitación: aproximación al aprendizaje en ingeniería de sistemas (2019)
This article describes the parallel comparative results of a study conducted in the Systems Engineering degree with simultaneous Programming groups (per semester). With one group, learning was adopted from codes already published and in operation; with theother, the traditional methodology of teaching programming through lectures was applied. This study was implemented with 16 programming groups during the years 2016, 2017, 2018 and 2019. Themethodologywasadjusted to a comparative case study, so that in each semester the results of the work with codes already written were analyzed in comparison with the results of groups that did the same but with codes written by the same students. The parallel courses were of different subjects. The quantitative results allowed qualitative inferences to be made in relation to learning through observation and direct interaction with students. The conclusion is that when the student has the appropriate knowledge base, the support provided by properly codified programs seems to accelerate and solidify the learning process with meaning, relevance and connectivity facilities.